OPTIMIZATION OF IN VITRO MICROPROPAGATION PROTOCOL OF THE ENDEMIC, ENDANGERED SPECIES AMYGDALUS LEDEBOURIANA FOR CONSERVATION - Islamova, S.S.; Nurtaza, A.S.; Dyussembekova, D.A.; Narmakhan, K.N.; Sadakova , B.D.; Serkebayev , A.S.; Kakimzhanova, A.A. (Eurasian Journal of Applied Biotechnology, 2025)
The article presents the results of a study on the in vitro conservation of the rare and endangered species Amygdalus ledebouriana. This almond species is noted for its high resistance to drought and low temperatures, as well as the nutritional value of its fruits. Prior to this study, no research had been conducted on the micropropagation of Amygdalus ledebouriana. In the present work, the authors developed an effective protocol for explant sterilization and establishment in vitro culture. A 9% hydrogen peroxide solution applied for 5 minutes was selected as the most suitable sterilizing agent, ensuring up to 75% explant viability. For shoot multiplication, the QL nutrient medium supplemented with 0.25 mg/L 6-benzylaminopurine (BAP) was optimized, resulting in an average of 7.24 shoots per explant. To date, 400 microshoots have been successfully propagated. An in vitro collection has been established from three natural populations of Amygdalus ledebouriana.